Perancangan Sistem Informasi Pengarsipan pada Dinas Perhubungan Provinsi Sumatera Utara Berbasis Website - Ruth Magdalena; Eva Julia Gunawati Harianja; Gortap Lumbantoruan; Eviyanti Novita Purba (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2026)
Mail archive management is an important part of supporting smooth administration in government agencies. However, manual archiving often causes various problems, such as delays in document retrieval, the risk of losing archives, and low work efficiency. This study aims to design a website-based document archiving information system for the North Sumatra Provincial Transportation Agency. The research methods used include observation, interviews, and literature study. The system design was carried out using Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), database design, and user interface design. The results of the study show that the designed information system is capable of improving document storage security. Thus, this system is expected to support improved administrative performance within the North Sumatra Provincial Transportation Agency.